Mucinous adenocarcinoma of the endometrium with metastasis to the clitoral glans after pelvic exenteration for radiation resistant vaginal cuff recurrence - Odinaka Mogor; Emily Hargrave; Demarreta Rush; Kenneth Hatch (Elsevier, 2019)
Mucinous adenocarcinoma of the endometrium (MACE) is a rare subtype of endometrial adenocarcinoma that often presents a significant diagnostic challenge due to its variation from the conventional morphologic appearance of endometrioid epithelium. This case report is of a woman who has survived 4 years after pelvic exenteration and subsequent vulvectomy for recurrent MACE.